2009
DOI: 10.1016/j.icarus.2009.04.030
|View full text |Cite
|
Sign up to set email alerts
|

2006 Fragmentation of Comet 73P/Schwassmann-Wachmann 3B observed with Subaru/Suprime-Cam

Abstract: a b s t r a c tThe fragmentation of the split Comet 73P/Schwassmann-Wachmann 3 B was observed with the primefocus camera Suprime-Cam attached to the Subaru 8.2-m telescope. The fragmentation revealed dozens of miniature comets [Fuse, T., Yamamoto, N., Kinoshita, D., Furusawa, H., Watanabe, J., 2007. Publ. Astron. Soc. Jpn. 59 (2), 381-386]. We analyzed the Subaru/Suprime-Cam images, detecting no fewer than 154 mini-comets, mostly extending to the southwest. Three were close to the projected orbit of fragment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
(74 reference statements)
1
21
0
Order By: Relevance
“…A good example event was observed at 73P/Schwassmann-Wachamann 3, in which the comet nucleus was ground into 10-100 m bodies. The power exponents of the cumulative size distribution of the fragments was ∼−2.3 (Ishiguro et al 2009;Fuse et al 2007). If the splitting is a principal mechanism in determining the size distribution of comet nuclei, the size distribution of PDCs might be steeper than the value we derived for PDCs.…”
Section: Discussion Of the Size Distribution Of Pdcsmentioning
confidence: 99%
“…A good example event was observed at 73P/Schwassmann-Wachamann 3, in which the comet nucleus was ground into 10-100 m bodies. The power exponents of the cumulative size distribution of the fragments was ∼−2.3 (Ishiguro et al 2009;Fuse et al 2007). If the splitting is a principal mechanism in determining the size distribution of comet nuclei, the size distribution of PDCs might be steeper than the value we derived for PDCs.…”
Section: Discussion Of the Size Distribution Of Pdcsmentioning
confidence: 99%
“…We considered the energy balance on the surface of the icy body given by (Desvoivres et al 1999(Desvoivres et al , 2000Ishiguro et al 2009)…”
Section: Discussion and Summarymentioning
confidence: 99%
“…As a result of these studies, we found that the power index of the size distribution of almost all comets would be in the range of −4 and −3 (Fulle 2004). We would like to emphasize that the power indices for the debris associated with comet outbursts are also in this range, that is, −3.7 < q < −3.3 for 29P/Schwassmann-Wachmann 1 (Moreno 2009) and −3.4 < q < −3.3 for 73P/Schwassmann-Wachmann 3B (Ishiguro et al 2009). Therefore, we will adopt an assumption of −4 < q < −3.…”
Section: Mass Erosionmentioning
confidence: 92%
“…By switching to differential size-frequency distributions of −1.84 on 73P small fragments and −2.56 on 73P large fragments, Reach et al (2009) compare 73P results with fragments of comet C/1999 S4 LINEAR (−2.72, as from Mäkinen et al 2001), as well as with fragments derived from the Kreutz group of cometary Sungrazers (−2.7 to −3.0, as from Sekanina 2003), indicating how 73P fragments presents the shallowest power-index slope. Nevertheless, Ishiguro et al (2009) used Subaru/Suprime-Cam data to derive a power-law index of the differential size distribution for 73P of −3.34, which is particularly higher with respect to Reach et al (2009) measurements. This difference may be explained by the fact that the power index of these split fragments has large uncertainties associated with contaminations of dust grains surrounding these objects.…”
Section: The Comparison Between 103p Boulders and Split Fragments Fromentioning
confidence: 99%